IN VITRO MULTIPLICATION OF VANGUERIA EDULIS AS AFFECTED BY CYTOKININS AND MEDIUM TYPE - H. El-Bagoury; A. Sarhan; F. Saadawy; Mai Ebrahim (Scientific Journal of Flowers and Ornamental Plants, 2018)
This work was carried out in the Tissue Culture Laboratory, Horticulture Research Institute, Agricultural Research Center, Giza, Egypt during the period from 2015 to 2017, to investigate the effect of cytokinin type and concentration (BAP, 2-iP and kin, at either 0.0, 1.0, 2.0 and 3.0 ppm) as well as medium type (MS or B5) on micro-shoots multiplication of in vitro cultured rare ornamental plant, Vangueria edulis. Results that were significant could be briefed in the following: the first position was obtained by BAP at 1 ppm in regard to survival %, shoot length and shooting %; BAP at 3 ppm for shoot number, leaf number and shoot length; 2-iP at 1 ppm for shooting %; 2-iP at 2 ppm for shoot length and shooting %; and kinetin at 2 ppm for survival %. Using MS medium gave rise to higher values concerning survival %, shoot number, leaf number, shoot length and shooting % compared to using B5 medium. The highest position was occupied by the combinations between BAP 1 ppm + MS for survival %, shoot number, shoot length and, shooting %; BAP 2 ppm + MS for shoot number; BAP 3 ppm+B5 for shoot number and leaf number; 2-iP 1 ppm + MS for shooting %; 2-iP 2 ppm + MS for shoot number; kinetin at 1 or 3 ppm + MS for shoot length and kinetin 2 ppm + MS for survival % and shoot length. It is recommended to treat in vitro produced micro-shoots of Vangueria edulis with BAP at 1 ppm + MS medium to obtain the highest values during multiplication stage.